EXAMINING THE EFFICACY OF PROJECT-BASED LEARNING AMONG UNIVERSITY STUDENTS - Mimin Aminah; Ida Maulida (Institut Pendidikan Tapanuli Selatan, 2021)
Learning is an active process that involves many components that determine learning achievement. One aspect that can turn into measurement indicator of success are learning method and the students themselves. Nevertheless, students are performers as well as determinants of the learning achievement. Student involvement in learning is a necessity, both in the form of attention and producing a product. Especially in online learning during the pandemic, students are required to have more engagement in seeking an understanding of learning. Furthermore, Project-Based Learning (PBL) is one of the alternative solutions that was conducted in this research. PBL is one of the teaching methods that is considered the most ideal to be applied in productive skills courses. As well to facilitating evaluation, PBL will also be able to support the needs of students to